The obesity epidemic: can we turn the tide? - Campbell, I (2003)
Obesity has reached epidemic proportions in the UK. It is important because of the associated co-morbidities, which include cardiovascular disease, type 2 diabetes, and osteoarthritis. The prevalence of obesity has increased because of a combination of excessive calorific intake (for example, from increased intake of energy dense foods) and insufficient energy expenditure (associated with a sedentary lifestyle). Weight loss of 5–10%, which can be achieved in primary care, is associated with significant health benefits. Obesity treatment in primary care includes lifestyle modification and drug treatment. The prevention and treatment of obesity cannot, however, be left solely to health professionals. Action is needed by government, the food industry, and society as a whole.